Strategy for Promoting Mass Literacy for Sustainable Development of Rural Communities in Niger State, Nigeria - Bello, Etsu Abubakar; Mohammed, Abdullahi; Maimuna, Usman; Abida, Rabiu Magem (NIU Journal of Social Sciences, 2026)
The study investigated strategy for promoting mass literacy for sustainable development of rural communities in Niger State. The objectives of the study were to investigate mass education, mass media, mass literacy campaigns and volunteerism as a strategy for promoting mass literacy for sustainable development of rural communities in Niger State. Three research questions asked and three hypotheses were tested at 0.05 level of significance. The study adopted a descriptive survey research design, while the study was carried out in Niger State. The population of the study was comprised of 34 adult education experts and 406 community development committee chairmen in Niger South Senatorial districts. Census was used to engage all adult education experts in the study. However, simple random sampling technique was used to select 267 community development committee chairmen in the eight local governments in Niger south senatorial district. The instrument for data collection was a closed ended questionnaire structured in fourpoint rating. The instrument was face and content validated by experts in adult education. The reliability of the instrument was established using Cronbach Alpha Reliability, which yielded an average coefficient value of 0.73. The data collected from the respondents were analyzed using mean and standard deviation. Finding of the study revealed that printed and non-printed information, adult education helps in achieving socio economic development for better status of rural people. Government, community heads and youth leaders should consistently carry out mass education programmes in their various communities. This will help to increase the rate of literacy among rural people. Keywords: Promoting, mass literacy, sustainable, development, rural, communities